Differential Output of the High-Sensitivity Rod Photoreceptor: AII Amacrine Pathway - PETRIDES, ARTEMIS (2008)
In the mammalian retina, the scotopic threshold of ganglion cells is in part dependent on how rod inputs are summed by their presynaptic cone bipolar cells. For ON cone bipolar cells, there are two anatomical routes for rod signals: 1) cone photoreceptors receive inputs via gap junctions with the surrounding, more numerous rods; and 2) ON cone bipolar cells receive highly convergent input via gap junctions with AII amacrine cells, which each receive input from hundreds of rods. Rod-cone coupling is thought to be utilized at higher photon fluxes relative to the AII-ON cone bipolar pathway due to the impedance mismatch of a single small rod driving a larger cone. Furthermore, it is widely held that the convergence of high-gain chemical synapses onto AIIs confers the highest sensitivity to ON cone bipolar cells and ganglion cells. A lack of coupling between one or more types of ON cone bipolar cells and AIIs would obviate this high-sensitivity pathway and explain the existence of ganglion cells with elevated scotopic thresholds. To investigate this possibility, we examined Neurobiotin and glycine diffusion from AIIs to bipolar cells and found that approximately one-fifth of ON cone bipolar cells are not coupled to AIIs. Unlike AII-AII coupling, which changes with ambient background intensity, the fraction of noncoupled ON cone bipolar cells was unaltered by dark or light adaptation. These data suggest that one of five morphologically distinct ON cone bipolar cell types is not coupled to AIIs and suggest that AII-ON cone bipolar coupling is modulated differently from AII-AII coupling.